COCONUT STEM UTILIZATION IN INDONESIA - Hastjarjo Sumardjan (International Coconut Community, 1989)
Coconut stem has been utilized in every coconut producing country in some form or other. Its utilization varies widely from small bridges to houses, furnitures and works of art. In Indonesia it is used mainly in Java, the most densely populated island. In other islands it is rarely used except for foot bridges because of two reasons. First, the farmers are reluctant to fell their coconut trees for its yield, however, small it is. Second, there is still enough supply of forest wood.